Physiotherapists Both Reproduce and Resist Biomedical Dominance when Working With People With Low Back Pain: A Qualitative Study Towards New Praxis. (May 2022) - Mescouto, Karime; Olson, Rebecca E; Hodges, Paul W; Costa, Nathalia; Patton, Mary Anne; Evans, Kerrie; Walsh, Kelly; Lonergan, Kathryn; Setchell, Jenny
Despite recommendations to incorporate physical and psychosocial factors when providing care for people with back pain, research suggests that physiotherapists continue to focus on biological aspects. This study investigated how interpersonal and institutional norms influence this continued enactment of the biological aspects of management. We used theoretically-driven analysis, drawing from Foucauldian notions of power, to analyse 28 ethnographic observations of consultations and seven group discussions with physiotherapists. Analysis suggested that physiotherapy training established expectations of what a physiotherapist 'should' focus on, and institutional circumstances strongly drew the attention of physiotherapists towards biological aspects. Resistance to these forces was possible when, for example, physiotherapists reflected upon their practice, used silences and pauses during consultations, and actively collaborated with patients. These circumstances facilitated use of non-biomedical management approaches. Findings may assist physiotherapists to rework the enduring normative focus on biomedical aspects of care when providing care for patients with back pain.